Sociology of Bugis Society: An Introduction - Mr. Ahmadin (Rayhan Intermedia, 2021)
This paper describes the socio-cultural heritage of the Bugis people in South Sulawesi from the perspective of sociology. The study approach in this research is historical sociology, which is intended to explore the socio-cultural values ​​of the past as a legacy that needs to be preserved. The life of the Bugis people throughout its history is very interesting to study, at least as a comparison with the reality of life now, namely after one of the ethnic groups in Sulawesi Province was influenced by modernization. This sociological study of Bugis society begins with a brief description of Bugis people and the world, social interactions, kinship systems, social stratification, social mobility, and social changes in Bugis society. Contact with the outside world and the Bugis people's penchant for wandering, caused this ethnic group to develop rapidly and even history records that the Bugis people built a center of government and became rulers of the kingdom in the archipelago.